The Inventory Control of Disposable Medical Materials in The Inpatient Installation of X Private Hospital in Central Java - Rachel Karimah; Chriswardani Suryawati; Septo Pawelas Arso (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The hospital pharmacy is one of revenue center, besides 50% of all income derived from hospital management pharmaceutical supplies..The implementation of the inventory control the disposable material in hospitals is still done manually without any method of special calculations. The purpose of this study is to analyze the inventory control of disposable medical materials in the inpatient installation of X private Hospital, in Central Java. This research is the qualitative study with those great case study aimed to locate and understand what is behind the phenomenon. This research was conducted at X Hospital in Central Java from August to December 2022. The sample of this research is 8 informants. Collecting data in this study with in-depth interviews. Analysis of the research data is data reduction, data presentation and drawing conclusions. The results of the study did not find any special calculation method and still found accumulation of disposable materials in several inpatient wards. The obstacle that most contributed to hindering the planning process was the absence of average usage data in one month because there was no reporting from the user. Therefore, it can be concluded that the availability control at X Private Hospital in Central Java is not in accordance with the guidelines issued by the Ministry of Health. it is suggested to the hospital to create a recording and reporting system regarding the use of consumable medical materials and it is necessary to have standard operating procedures and policies for the use of consumable medical materials in inpatient wards so that effective and efficient availability control can be carried out. Keyword: Disposable Medical Materials, Inventory Control, Logistics Management, Pharmaceutical Installation